Implementation of Wall Slide Exercise (WSE) and Neuromuscular Taping (NMT) for Post Reconstruction of Anterior Cruciate Ligament (ACL): Case Report - Yose Rizal; Iit Selviani; Ruswaldi Munir; VIna Eka Prasetiani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Anterior Cruciate Ligament (ACL) injury is one of the most common knee injuries. ACL tears are more common when pivoting and abrupt direction shifts. Ruptures of the anterior cruciate ligament (ACL) can lead to aberrant knee joint mechanics and persistent degenerative joint change, torn meniscus, cartilage loss, and other knee. The role of physiotherapy in post-operative cases of ACL reconstruction is very important to avoid various possibilities that arise post-surgery, such as limited joint range of motion (stiffness), muscle weakness, swelling for a long time, and so on. A 24-year-old male patient as footballer came to Fisiohands Clinic, Pekanbaru, complaining of pain and stiffness in the knee. The history of the case as the patient played football and fell with the worst position leg in February 2024. The patient underwent surgery at a hospital in Pekanbaru city and then chose to undergo physiotherapy at the physio hands clinic. Rehabilitation training was carried out for 2 weeks. Before starting exercise, vital signs are checked first to clarify the patient's general condition. The training program is a combination of Wall Slide Exercise (WSE) and Neuromuscular Taping (NMT) for 2 weeks. Several physical examinations were performed, including a Goniometer range of motion assessment and a Visual Analogue Scale assessment for knee pain. Exercises for the rehabilitation of the anterior cruciate ligament (ACL) after surgery help to lessen discomfort and improve joint range of motion. After ACL reconstruction, the knee joint range of motion was improved and pain was reduced with physiotherapy intervention that included six sessions of Neuromuscular Taping (NMT) and Wall Slide Exercise (WSE).